PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS (Sub Sektor Hotel, Restaurant, Dan Pariwisata yang terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Septiani, Desy (Peneliti.net, 2024)
Financial difficulties are the company's financial situation prior to bankruptcy. This research was conducted at hotel, restaurant and tourism sub-sector service companies listed on the Indonesia Stock Exchange (IDX) for 2019-2022. The purpose of this study is to predict how many companies are experiencing Financial Distress and Non-Financial Distress, to find out how many companies are able to generate profits during a pandemic, and to find out whether profitability (ROA), leverage (DER), and liquidity (CR) are related to financial distress. influence on research objects in hotel, restaurant and tourism industry service companies listed on the Indonesia Stock Exchange (IDX) in 2019-2022. This study used a purposive sampling technique. Methods of data analysis using logistic regression analysis. The data was processed using SPSS 27. The results of this study indicate that profitability as measured using return on assets (ROA) has a significant impact on financial distress in a negative direction because return on assets (ROA) get a negative beta value of -29,510 with a significance value (sig) of 0,000, it can be concluded that the sig value <0.05, leverage as measured using the debt to equity ratio (DER) has no significant impact on financial distress in a negative direction because Debt to equity ratio (DER) gets a negative beta value of -0.001 with a significance value (sig) of 0.927, it can be concluded that the sig value > 0.05, and liquidity as measured by the current ratio has no significant impact on financial distress in a negative direction because the Current ratio (CR ) get a beta value of -0.005 with a significance value (sig) of 0.723, it can be concluded that the sig value > 0.05.